(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Metaphors have long been topic of interest for the scientists of many spheres. Recent emerge of cognitive linguistics gave life to a new approach to metaphors, researching them from different angles. This article is devoted to the realization of conceptual or cognitive metaphors in linguistic context with the help of bright examples. It outlines basic notions related to the topic. It is known that metaphors are the main conceptual domain in cognitive linguistics. It refers to the understanding of one idea in terms of another.